Analisis Kinerja Keuangan dan Manajemen Risiko terhadap Return Saham pada Perusahaan Perdagangan, Jasa dan Investasi yang Listing di BEI Tahun 2012-2016 - Kusmeri; Jaka Waskito (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2017)
Financial Performance Analysis and Risk Management Against Stock Returns on Trading, Service and Investment Companies Listed on the Indonesia Stock Exchange for 2012-2016. Essay. Tegal: Faculty of Economics, Pancasakti University Tegal. 2017. The problem in this study is whether there is an influence of liquidity ratios, leverage, activity, profitability and risk management both individually and jointly on stock returns in trading, service and investment companies that are listed on the IDX in 2012-2016. The purpose of this study is to analyze the effect of liquidity ratios, leverage, activity, profitability and risk management both individually together on stock returns in trading, service and investment companies that are listed on the IDX in 2012-2016. This research hypothesis is thought to have an influence on liquidity, leverage, activity, profitability and risk management ratio both individually and jointly on stock returns in trading, service and investment companies that are listed on the Indonesia Stock Exchange for 2012-2016. The data collection method used in this study is documentation. While the data analysis method used is descriptive analysis, classic assumption test, simple regression analysis, simple linear regression significance test, multiple regression analysis, significance test of multiple linear regression and coefficient of determination. From the results of the study, it can be seen that there is a positive and significant effect of partial liquidity ratios on stock returns. From the results of the study it can be seen that there is a positive and significant effect of the leverage ratio partially on stock returns. From the results of the study it can be seen that there is a positive and significant effect of the activity ratio partially on stock returns. From the results of the study, it can be seen that there is a positive and insignificant influence on the profitability ratio partially towards stock returns. From the results of the study, it can be seen that there is a negative and insignificant effect of partial risk management on stock returns. From the results of the study it can be seen that there is a positive and significant effect of liquidity, leverage, activity, profitability and risk management ratio together towards stock returns.